Expression of Metallothionein, P53 and Antioxidant Enzymes by Selenium and Vitamin D3 during Diethyl Nitrosamine-Induced Rat Liver Preneoplasia: Effect of selenium on nitrosamine-induced rat liver preneoplasia - N Thirumoorthy; A Shyam Sunder; L Panayapan; KT Manisenthil Kumar; M. Senthil Kumar; GNK Ganesh; Soundera Pandian; Malay Chatterjee (Iranian Journal of Pharmaceutical Sciences, 2010)
Many studies have proved that the dietary micronutrient has an inhibitory effect against experimentally induced rat hepatocarcinogenesis. The present work is an attempt to understand combined effect of selenium (Se) and vitamin D3 (vit D3) on some potential protein expression markers of carcinogenesis, such as metallothionein (MT), P53 and antioxidant levels during diethyl nitrosamine (DEN) induced (200 mg/kg in 0.9% NaCl; IP) rat liv er preneoplasia. In a short term regimen combined supplementation of Se and vit D3 at a dose of 8 ppm in water and 0.3 μl/100μl in propylene glycol, respectively, suppressed the formation of DNA comets (28.40%), thereby indicating its non- genotoxicity at this particular dose. Se and vit D3 administration throughout the study reduced relative liver weight. Modular incidence were 22.7% when compared to the carcinogen control. However, treatment with Se and vit D3 showed significant expressions of MT and P53 which studied at four sequential time points. An increased immunopositive of P53 protein (1.3±0.56% p<0.02) was found in Se and vit D3 together treated rat liver with an elevated apoptotic labeling index (A1; p<0.001) as documented by TUNEL assay. The positive results of MT expression at various time intervals suggest that, Se and vit D3 together mediated suppression of MT may be associated with induction of apoptosis. The results thus provide evidence for the first time in support of the potential role of combined supplementation of Se and vit D3 on induction of P53 apoptosis with concurrent suppression of MT in order to have an understanding. Regardless of the mechanism, based on the results reported in this study, both Se and vit D3 could be considered a potential cancer chemopreventive agents whose effect is presumably based on inhibition of growth of the neoplastic cells by coordinated regulations of different biochemical markers and enzymes studied herein.